An Elderly Thyrotoxic Patient presented with anorexia complicated to cardiac arrest (Bangladesh Journal of Medicine, 2015)
Hyperthyroidism is a common endocrine disorder. Earlier this disorder had been found in the young to middle age group, whereas it is now well recognized in elderly. Young patients generally presented with typical symptoms and signs where it can be diagnosed easily. But in elderly the presentation is varied and often atypical. Among the older adults the diagnosis is often overlooked or missed as many patients presented with uncommon symptoms. Here an elderly presented with anorexia that subsequently developed thyrotoxic crisis followed by cardiac arrest (due to hypokalaemia) and multi-organ dysfunction syndrome in the background of urinary tract infection.Bangladesh J Medicine Jan 2014; 25 (1) : 29-30